Preparation method and application of high-stability catalyst for preparing synthesis gas through methane dry reforming
The Ni-Si-Al-O catalyst prepared by the one-pot method adjusts the Ni particle size and metal-support interaction force by doping the auxiliary Si, which solves the problem of sintering and carbon deposits of traditional catalysts under high temperature reaction conditions, and significantly improves the activity and stability of the methane dry reforming reaction.
Patent Information
- Application Number
- CN202510079612.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional methane dry reforming catalysts are prone to sintering under high temperature reaction conditions, resulting in high reaction inactivation rate and Ni particles are prone to carbon accumulation, affecting the stability of the reaction.
The integrated catalyst Ni-Si-Al-O was prepared by a one-pot method. By doping the additive Si, the particle size of Ni particles and the metal-support interaction force were adjusted to improve the stability of the catalyst and the resistance to carbon deposits.
At 700°C, the methane conversion rate was increased by 15%, the carbon dioxide conversion rate was increased by 12%, and the CH4 and CO2 conversion rate of the catalyst was almost not reduced within 20 hours, which significantly improved the activity and stability of the catalyst.
Smart Images

Figure BDA0005248136860000072 
Figure BDA0005248136860000073 
Figure BDA0005248136860000081
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a highly stable catalyst for producing synthesis gas by dry reforming of methane. Specifically, it is a catalyst for converting two main greenhouse gases, CO2 and CH4, into synthesis gas (CO and H2) through reforming reaction, and belongs to the field of waste gas treatment technology and environmental catalytic environment. Background Art
[0002] Methane conversion technology, as an efficient, green, and low-carbon energy technology, is of great significance in today's situation. In particular, methane dry reforming technology, a process that can effectively convert greenhouse gases CO2 and CH4 into synthesis gas, can be used as a fuel for power generation or as a raw material for various production processes, depending on the ratio of H2 and CO in the synthesis gas.
[0003] Compared with traditional steam reforming and partial oxidation syngas production processes, methane dry reforming has several significant advantages. First, methane dry reforming provides a valuable opportunity for the capture and utilization of carbon dioxide (a major greenhouse gas) by using carbon dioxide (a major greenhouse gas) as a reactant instead of water in steam reforming, thereby providing a potential solution to reduce greenhouse gas emissions. In addition, with the discovery of shale gas reserves and advances in hydraulic fracturing technology, the supply of methane resources has increased significantly. In addition to shale gas, biogas and landfill gas (both produced by anaerobic decomposition) are also important sources of carbon dioxide and methane and can be used in the methane dry reforming process.
[0004] Methane dry reforming technology needs to be carried out at a very high reaction temperature. Nickel metal is the only cheap transition metal with catalytic performance comparable to that of precious metals. Among methane dry reforming catalysts, the active metal-support interaction of supported Ni catalysts is weak. Under high temperature reaction conditions, Ni particles are easily sintered, resulting in a high reaction deactivation rate. Ni is prone to carbon deposition under methane dry reforming conditions, resulting in reduced reaction stability.
[0005] The design idea of this patent is to prepare a green monolithic catalyst with high stability, anti-sintering, strong interaction between active metal and carrier through a simple preparation method and low-cost raw materials. The literature reports that the impregnation method is more convenient to prepare supported catalysts, but it is difficult to meet the high activity and stability points by using the impregnation method to prepare Ni / SiO2 or Ni / Al2O3. The literature reports that the auxiliary agent Si can stabilize the structure of Al2O3, and a small amount of Si reduces the Lewis acidity of alumina, thereby improving the stability and activity of the reaction. Therefore, the literature also reports that ZSM-5 molecular sieves with different Si / Al ratios are used as carriers to load Ni to prepare supported catalysts Ni / ZSM-5. It was thought that this would be very effective. No matter which ZSM-5 molecular sieve with different Si / Al ratios is used for loading, the stability of the reforming catalyst cannot be significantly improved. Literature reports that the one-pot method can significantly improve the activity and stability of the catalyst. Therefore, the monolithic catalysts Ni-Si-O and Ni-Al-O were synthesized by the one-pot method. It was found that Ni-Al-O has high stability but low activity. On the basis of the Ni-Al-O catalyst, the auxiliary agent Si was further introduced. The Ni / Si-Al-O catalyst also has high stability but low activity. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of a catalyst with strong stability for preparing synthesis gas by dry reforming of methane. The method has the advantages of simple process, easy operation and low cost. First, low-cost SiO2 and γ-Al2O3 are used as carriers, Ni is used as an active component, and aluminum isopropoxide is used as a framework raw material. The monolithic catalyst Ni-Si-Al-O is prepared by a one-pot method, and the particle size of Ni particles and the interaction between metal and carrier are regulated by doping with auxiliary agent Si and adjusting the addition amount of auxiliary agent Si, so as to improve the stability and anti-carbon deposition performance of the catalyst. All components are mixed at the same time in the same reaction environment, and the active components are highly evenly distributed, and the active components have a strong interaction with the carrier. More uniform active components enhance the adsorption capacity of the catalyst for CH4 and CO2, thereby improving the catalytic activity and stability of the catalyst. Stronger interaction can inhibit the sintering of active components under high temperature reaction conditions and extend the service life of the catalyst. The one-pot method for preparing the Ni-Si-Al-O monolithic catalyst containing auxiliary agent Si for methane dry reforming catalysis is rarely reported. The first problem solved by the present invention is to develop a highly stable catalyst with independent intellectual property rights; the second problem solved by the present invention is to regulate the particle size of Ni particles and the interaction between metal and carrier, so that the catalyst has high activity, stability and anti-carbon deposition ability at 700°C; compared with the unmodified supported catalyst Ni / Al2O3, the methane conversion rate at 700°C is 76% (increased by 15%), and the carbon dioxide conversion rate is 72% (increased by 12%). The 20-hour stability evaluation shows that the CH4 and CO2 conversion rates of the catalyst are almost reduced.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is:
[0008] A preparation method and application of a highly stable catalyst for producing synthesis gas by dry reforming of methane, comprising the following steps:
[0009] (1) Weigh the active components in a stoichiometric ratio (the total mass of the carrier and the active component Ni is 100%, the mass percentage of the active component Ni in the catalyst is 10%, and the total mass of the additive and the carrier is 90%), nickel nitrate hexahydrate (Ni(NO3)2·6H2O) as the active component Ni source, and the additive ethyl orthosilicate (C8H 20 O4Si) as the auxiliary Si source, aluminum isopropoxide (C9H 21 AlO3) is the Al source of the main framework material. Ni(NO3)2·6H2O is added to deionized water and stirred until it is completely dissolved to obtain a transparent solution;
[0010] (2) The total mass of the additive and the carrier in step (1) is 90%, which can be divided into 1%, 3%, 5%, 7%, and 9% of the total mass of the Si source, which respectively correspond to 89%, 87%, 85%, 83%, and 81% of the total mass of the main frame Al. The following preparation method takes 5% Si and 85% Al as an example. Except for the different proportions, the preparation method is exactly the same.
[0011] (3) The C9H measured in step (2) 21 AlO3 was added to anhydrous ethanol and a constant temperature magnetic stirrer was closed for 20 min to obtain a white solution;
[0012] (4) The weighed C8H 20 O4Si was added to the white slurry obtained in step (3); a constant temperature magnetic stirrer was closed for 20 minutes to obtain a mixed solution;
[0013] (5) adding the transparent solution obtained in step (1) to the mixed solution obtained in step (4), and stirring in a closed constant temperature magnetic stirrer for 20 minutes to obtain a mixed solution;
[0014] (6) opening the sealed mold of the mixed slurry obtained in step (5), and rotating and stirring in a constant temperature heated magnetic stirrer until evaporated to dryness to form a powder;
[0015] (7) placing the powder obtained in step (6) in an oven and drying overnight to obtain a green powder;
[0016] (8) The powder obtained in step (7) is placed in a muffle furnace, calcined, naturally cooled to room temperature, pressed into tablets, and ground into 20-40 mesh catalysts to obtain a methane dry reforming catalyst for producing synthesis gas.
[0017] According to the above scheme, the activation method is calcination.
[0018] According to the above scheme, the mass percentage of the carrier is 100%, and the mass percentage of the active component Ni is 10%.
[0019] According to the above scheme, the temperature of the closed constant temperature magnetic stirrer for 20 minutes is 20°C.
[0020] According to the above scheme, the mixture is stirred in a constant temperature heated magnetic stirrer until it is evaporated to dryness and forms a powder; the temperature is 80°C;
[0021] Preferably, the drying temperature is 110°C;
[0022] The drying time is 11-13h;
[0023] The calcination temperature is 700°C;
[0024] The calcination time is 5 hours.
[0025] The present invention also provides the use of a catalyst for producing synthesis gas from methane dry reforming prepared by the preparation method described in any one of the above technical solutions in the conversion of carbon dioxide.
[0026] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0027] 1. The one-pot method of the present invention is used to prepare the Si-doped Ni-based catalyst Ni-5%Si-Al-O for CH4 / CO2 reforming reaction. The catalytic activity of the catalyst is significantly improved compared with the Ni-based catalyst prepared by impregnation. At 700°C, the initial conversion rates of methane and carbon dioxide reach 76% and 72%, respectively, which are significantly improved compared with conventional Ni / SiO2 and Ni / Al2O3 catalysts. The stability evaluation of 20 hours shows that the CH4 and CO2 conversion rates of the catalyst are almost not reduced.
[0028] 2. A Ni-5% Si-Al-O catalyst was prepared by a one-pot method. The preparation method has a simple process, low cost, high catalytic activity for methane dry reforming reaction, strong stability, and low carbon deposition, which is suitable for industrial production.
[0029] Figure 1 These are test graphs of the catalytic performance of the catalysts prepared in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0030] Figure 2 These are the XRD spectra of the catalysts prepared in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0031] Figure 3 H2-TPR spectra of the catalysts prepared in Examples 1, 2, 3, 4, 5, 7, 8 and 9.
[0032] Figure 4 The XPS spectra of the catalysts prepared in Examples 1, 2, 3, 4, 5, and 8 are shown. DETAILED DESCRIPTION
[0033] The present invention will be further described below through some implementation examples, but the present invention is not limited thereto.
[0034] Example 1
[0035] The preparation steps for methane dry reforming catalyst are as follows:
[0036] Weigh 0.991g Ni(NO3)2·6H2O in a beaker, add 30ml deionized water to dissolve it, add 1.8g SiO2 carrier, soak at room temperature for 45min, dry in a water bath in a 80℃ constant temperature heating magnetic stirrer, then take it out and place it in a 110℃ oven for 12h; place it in a muffle furnace and roast it at 700℃ in air atmosphere for 5h, and crush the roasted powder into 20-40 mesh with a tablet press at a pressure of 8Mp to obtain a Ni / SiO2 catalyst. The catalyst composition of Example 1 is shown in Table 1.
[0037] Catalyst Evaluation
[0038] The stability evaluation of the catalyst was carried out in a homemade continuous flow fixed bed reactor. The reaction tube was a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature was measured by a thermocouple placed in the middle of the reaction tube and controlled by a programmed temperature controller. The gas flow was controlled by a mass flow meter and the space velocity was Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 1 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0039] Example 2
[0040] The catalyst Ni-Si-O was prepared by a one-pot method. A certain amount of 15 ml of deionized water and 25 ml of anhydrous ethanol were mixed and poured into a conical flask, and then 0.991 g of Ni(NO3)2·6H2O was added to the flask, 25 ml of ethyl orthosilicate was dripped into the flask, and the pH value was adjusted with ammonia water (dropped to pH≈9-10), and the beaker was sealed and stirred for 60 minutes. After that, the beaker was placed in a water bath in a constant temperature heated magnetic stirrer at 80°C for drying, and then taken out and placed in a 110°C oven for drying for 12 hours; it was placed in a muffle furnace and calcined at 700°C for 5 hours under an air atmosphere, and the calcined powder was crushed to 20-40 meshes by a tablet press under a pressure of 8Mp, and a Ni-Si-O catalyst was obtained. The catalyst composition of Example 2 is shown in Table 1.
[0041] Catalyst Evaluation
[0042] The evaluation method of Example 1 is as follows: The catalytic performance of the catalyst is evaluated in a self-made continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow rate is controlled by a mass flow meter, and the space velocity is Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 1 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0043] Example 3
[0044] Weigh 0.991g of Ni(NO3)2·6H2O in a beaker, add 30ml of deionized water to dissolve it, add 1.8g of γ-Al2O3, soak for 45min, dry in a water bath in a constant temperature heating magnetic stirrer at 80℃, then take it out and place it in a 110℃ oven for 12h; place it in a muffle furnace under air atmosphere at 700℃ for 5h, and crush the calcined powder into 20-40 mesh with a tablet press at a pressure of 8Mp to obtain a Ni / Al2O3 catalyst. The catalyst composition of Example 3 is shown in Table 1.
[0045] Catalyst Evaluation
[0046] The evaluation method of Example 1 is as follows: The catalytic performance of the catalyst is evaluated in a self-made continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow rate is controlled by a mass flow meter, and the space velocity is Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 2 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0047] Example 4
[0048] Dissolve 7.211g of aluminum isopropoxide in 120ml of anhydrous ethanol and stir for 20min. Add 0.991g of nickel nitrate hexahydrate (mass fraction of active component Ni is 10%) dissolved in 20ml of deionized water to the aluminum isopropoxide solution and stir for 40min. Dry in a water bath in a magnetic stirrer with constant temperature heating at 80℃, then take it out and place it in a 110℃ oven for 12h; place it in a muffle furnace and roast it at 700℃ in air atmosphere for 5h, and crush the roasted powder into 20-40 meshes with a tablet press at a pressure of 8Mp to obtain a Ni-Al-O catalyst. The catalyst composition of Example 4 is shown in Table 1.
[0049] Catalyst Evaluation
[0050] The evaluation method of Example 1 is as follows: The catalytic performance of the catalyst is evaluated in a self-made continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow rate is controlled by a mass flow meter, and the space velocity is Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 2 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0051] Example 5
[0052] 7.211g of aluminum isopropoxide was dissolved in 120ml of anhydrous ethanol and stirred for 20min, then 0.1g of tetraethyl orthosilicate (mass fraction of component Si is 5%) was added dropwise and stirred for another 20min, then the beaker was placed in a constant temperature magnetic water bath at 80°C and stirred until the liquid evaporated to powder form, and then dried in an oven at 110°C for 12h to obtain a carrier Si-Al-O. The obtained carrier was placed in a muffle furnace and calcined step by step, and finally kept at 700°C for 5h to obtain a carrier Si-Al-O. Weigh 0.991g of nickel nitrate hexahydrate (mass fraction of active component Ni is 10%) and add it to an appropriate amount of deionized water and stir to completely dissolve it, then add 1.85g of Si-Al-O, stir and mix well, soak at room temperature for 45min, dry in a water bath in a constant temperature heating magnetic stirrer at 80℃, then take it out and place it in a 110℃ oven and dry it for 12h; place it in a muffle furnace and roast it at 700℃ in air atmosphere for 5h, and crush the roasted powder into 20-40 mesh by a tablet press at a pressure of 8Mp to obtain a Ni / Si-Al-O catalyst. The catalyst composition of Example 5 is shown in Table 1.
[0053] Catalyst Evaluation
[0054] The evaluation method of Example 1 is as follows: The catalytic performance of the catalyst is evaluated in a self-made continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow rate is controlled by a mass flow meter, and the space velocity is Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 2 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0055] Example 6
[0056] 7.211g of aluminum isopropoxide was dissolved in 120ml of anhydrous ethanol and stirred for 20min, then 0.02g of tetraethyl orthosilicate (the mass fraction of component Si is 1%) was added dropwise and stirred for another 20min, 0.991g of nickel nitrate hexahydrate (the mass fraction of active component Ni is 10%) dissolved in 20ml of deionized water was added to the aluminum isopropoxide solution and stirred for 20min. The mixture was dried in a water bath in a magnetic stirrer heated at 80℃, then taken out and placed in a 110℃ oven for 12h; the mixture was placed in a muffle furnace and calcined at 700℃ for 5h under air atmosphere, and the calcined powder was crushed to 20-40 meshes by a tablet press under a pressure of 8Mp to obtain a Ni-1%Si-Al-O catalyst. The catalyst composition of Example 6 is shown in Table 1.
[0057] Catalyst Evaluation
[0058] The evaluation method of Example 1 is as follows: The catalytic performance of the catalyst is evaluated in a self-made continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow rate is controlled by a mass flow meter, and the space velocity is Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 2 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0059] Embodiments 7 to 10
[0060] Compared with Implementation Case 6, only the mass percentage of Si in the catalyst is different, that is, the mass percentage of Si is 3%, 5%, 7%, and 9%, respectively, and the remaining steps are exactly the same as Example 6.
[0061] Catalyst Evaluation
[0062] The evaluation method of Example 1 is as follows: The catalytic performance of the catalyst is evaluated in a self-made continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow rate is controlled by a mass flow meter, and the space velocity is Reaction raw gas: 24.2ml / min CH4, 26.4ml / min CO2, in the experiment, the catalyst dosage is 0.1g, the reaction temperature is 700℃, and sampling is performed every half hour. The gas composition of the reactants and products is analyzed by contour gas chromatograph (SC3000B) to calculate the conversion rate of CH4 and CO2. The conversion curve of the catalyst for CH4 and CO2 at different time points is shown in the figure below. Figure 2 As shown, the initial conversion rates of CH4 and CO2 are shown in Table 1.
[0063] Table 1 Molecular sieve catalyst composition and CH4, CO2 conversion rate and CO yield of specific examples:
[0064] Table 2 CH4 deactivation rate after catalyst reaction in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10:
[0065] XRD characterization
[0066] The XRD spectra of Examples 1, 2, 3, 4, 5, 7, 8 and 9 are as follows: Figure 2 As shown in Figure 4, NiO characteristic diffraction peaks appear at 2θ = 37.2°, 43.3°, 62.9°, 75.4° and 79.4° [PDF#47-1049]. Compared with conventional Ni / SiO2 and Ni / Al2O3 catalysts, the intensity of characteristic diffraction peaks of Ni-based catalysts doped with additive Si is significantly reduced, indicating that the doping of additive Si can improve the dispersion of Ni particles in the catalyst to a certain extent.
[0067] The reducibility of the fresh catalyst was studied by H2-TPR using BSD-Chem200. 0.06 g of the catalyst was weighed into a tube and stuffed with cotton. It was initially treated at 300 °C for about 30 min under argon and then at 10 °C min under 10% H2 / Ar. -1 The TPR measurement temperature was raised to 800°C at a heating rate of 30 min.
[0068] The H2-TPR spectra of the catalysts prepared in Examples 1, 2, 3, 4, 5, 7, 8 and 9 are shown in Figure 3 As shown in the figure, compared with the catalyst based on SiO2, the peak of the catalyst based on Al2O3 appears at a higher temperature, indicating that the active metal in the catalyst has a stronger interaction with the carrier.
[0069] The Ni in the catalyst was investigated using X-ray photoelectron spectroscopy (XPS, Thermo Scientific KAlpha+). 2+ Binding energy. The binding energy was also calibrated using C1s (Eb = 284.8 eV) as a standard.
[0069] The XPS spectra of the catalysts prepared in Examples 1, 2, 3, 4, 5, and 8 are as follows: Figure 4 As shown, Example 8 has a stronger binding energy to Examples 1, 2, 3, 4 and 5, indicating that the active metal in the catalyst and the carrier have a stronger interaction force.
Claims
1. A preparation method and application of a highly stable catalyst for producing synthesis gas by dry reforming of methane, characterized in that: The method comprises the following steps: (1) Weigh the active components in a stoichiometric ratio (the total mass of the carrier and the active component Ni is 100%, the mass percentage of the active component Ni in the catalyst is 10%, and the total mass of the additive and the carrier is 90%), nickel nitrate hexahydrate (Ni(NO3)2·6H2O) as the active component Ni source, and the additive ethyl orthosilicate (C8H 20 O4Si) as the auxiliary Si source, aluminum isopropoxide (C9H 21 AlO3) is the Al source of the main framework material. Ni(NO3)2·6H2O is added to deionized water and stirred until it is completely dissolved to obtain a transparent solution; (2) The total mass of the additive and the carrier in step (1) is 90%, which can be divided into 1%, 3%, 5%, 7%, and 9% of the total mass of the Si source, which respectively correspond to 89%, 87%, 85%, 83%, and 81% of the total mass of the main frame Al. The following preparation method takes 5% Si and 85% Al as an example. Except for the different proportions, the preparation method is exactly the same. (3) The C9H measured in step (2) 21 AlO3 was added to anhydrous ethanol and a constant temperature magnetic stirrer was closed for 20 min to obtain a white solution; (4) The weighed C8H 20 O4Si is added to the white slurry obtained in step (3); The thermostatic magnetic stirrer was closed for 20 min to obtain a mixed solution; (5) adding the transparent solution obtained in step (1) to the mixed solution obtained in step (4), and stirring in a closed constant temperature magnetic stirrer for 20 minutes to obtain a mixed solution; (6) opening the sealed mold of the mixed slurry obtained in step (5), and rotating and stirring in a constant temperature heated magnetic stirrer until evaporated to dryness to form a powder; (7) placing the powder obtained in step (6) in an oven and drying overnight to obtain a green powder; (8) The powder obtained in step (7) is placed in a muffle furnace, calcined, naturally cooled to room temperature, pressed into tablets, and ground into 20-40 mesh catalysts to obtain a methane dry reforming catalyst for producing synthesis gas.
2. The method for preparing a catalyst for producing synthesis gas by dry reforming of methane according to claim 1, characterized in that: The activation method is roasting.
3. The method for preparing a catalyst for producing synthesis gas by dry reforming of methane according to claim 1-2, characterized in that: The total mass of the auxiliary agent and the carrier is 90%, which can be divided into Si source accounting for 1%, 3%, 5%, 7%, and 9% of the total mass, respectively corresponding to the main frame Al accounting for 89%, 87%, 85%, 83%, and 81% of the total mass.
4. The method for preparing a catalyst for producing synthesis gas by dry reforming of methane according to any one of claims 1 to 3, characterized in that: The carrier is aluminum isopropoxide (C9H 21 AlO3) as raw material.
5. The method for preparing the catalyst for producing synthesis gas by dry reforming of methane according to any one of claims 1 to 4, characterized in that: The mass percentage of the carrier is 100%, and the mass percentage of the active component Ni is 10%.
6. The method for preparing the catalyst for producing synthesis gas by dry reforming of methane according to any one of claims 1 to 5, characterized in that: Taking the mass of the carrier as 100%, the mass percentage of the additive Si is 1%, 3%, 5%, 7%, and 9%.
7. The method for preparing the catalyst for producing synthesis gas by dry reforming of methane according to any one of claims 1 to 6, characterized in that: All were prepared by one-pot method.
8. The method for preparing the catalyst for producing synthesis gas by dry reforming of methane according to any one of claims 1 to 7, characterized in that: The stirring temperature is 80°C; the drying temperature is 110°C; and the drying time is 11-13h.
9. The method for preparing the catalyst for producing synthesis gas by dry reforming of methane according to any one of claims 1 to 8, characterized in that: The calcination temperature is 700°C and the calcination time is 5 hours.
10. Use of the catalyst for producing synthesis gas through dry reforming of methane according to any one of claims 1 to 9 in the conversion of carbon dioxide.
Citation Information
Cited By
Method and device for hydrogen production through methanol-to-aromatic hydrocarbon flue gas carbon dioxide methane reforming
CN121698304A